Developing a Social‑Media-Based Manufacturing Engineering Drawing Teaching Module to Improve Students’ Skills - Ahmad Raihan, Prajka; Wastira, Jarudin (Global Synthesis in Education Journal, 2025)
The increasing integration of technology in education has brought forth innovative ways to enhance the learning of complex skills. This study explores the development of a social-media-based teaching module for manufacturing engineering drawing aimed at improving students’ technical skills dynamically and engagingly. The research follows a design-based approach, utilizing the ADDIE (Analyze, Design, Develop, Implement, Evaluate) instructional design model to create a modular curriculum delivered through a social media platform (Instagram and YouTube). The study evaluates the effectiveness of this module by conducting a quasi-experimental pre-post test with 120 engineering students from a Vocational High School. Data were analyzed using paired-sample t-tests and qualitative thematic analysis to assess skill improvement and student engagement. Results indicate a statistically significant improvement in students’ manufacturing drawing skills, with an average skill gain of 15% (p < 0.001). Qualitative findings highlight the positive impact of social media on peer collaboration, real-time feedback, and increased engagement. The module’s design was validated through expert reviews, achieving a content validity index (CVI) of 0.88. The findings suggest that social media can provide an effective and scalable platform for teaching technical subjects, facilitating enhanced interaction and knowledge retention. This study contributes to the literature on technology-enhanced learning and offers practical recommendations for educators seeking to incorporate social media into manufacturing engineering curricula.